Projections of two-particle correlations onto transverse rapidity in Au + Au collisions at √ s N N = 200 GeV at STAR - STAR Collaboration (Physical Review C, 2022)
Two-particle correlation measurements projected onto two-dimensional, transverse rapidity coordinates (yT1,yT2) provide an independent, orthogonal view of the multidimensional correlation distribution that is most often studied via angular projections. As such, these independent transverse projections allow access to manifestations of dynamical fluctuations in relativistic heavy-ion collisions that angular-correlation measurements may not be sensitive to. We report nonidentified charged-particle correlations for Au+Au minimum-bias collisions at √sNN=200 GeV taken by the STAR experiment at the Relativistic Heavy-Ion Collider (RHIC). Correlations are presented as two-dimensional functions of transverse rapidity for like-sign, unlike-sign, and all charged-particle pairs, as well as for particle pairs whose relative azimuthal angles lie on the near-side, the away-side, or at all relative azimuth. The correlations are constructed using charged particles with transverse momentum pT≥0.15 GeV/c, pseudorapidity from −1 to 1, and azimuthal angles from −π to π. The significant correlation structures that are observed evolve smoothly with collision centrality. The major correlation features include a saddle shape plus a broad peak with maximum near yT≈3, corresponding to pT≈1.5 GeV/c. The broad peak is observed in both like- and unlike-sign charge combinations and in near- and away-side relative azimuthal angles. The all-charge, all-azimuth correlation measurements are compared with the predictions of hijing and epos to provide theoretical context for these new measurements. The results indicate that the correlations for peripheral to mid-central collisions can be approximately described as a superposition of nucleon + nucleon collisions with minimal effects from the quantum chromodynamics medium. Strong medium effects are indicated in mid- to most-central collisions.
Keywords: dept.phy; peer-reviewed